Revisiting the built environment: 10 potential development changes and paradigm shifts due to COVID-19 - Cheshmehzangi, Ali (2021)
This study explores potential development and paradigm shifts in two main sectors of construction and the built environment due to COVID-19. These development changes are discussed based on evidence from previous pandemics, current and expected impacts on both industries, and how they are likely to shape the next policy, practices, and perspectives. By assessing the primary areas of both sectors through an expert-led analysis, this study suggests 10 potential development changes that we could expect in the post-COVID time. These potential changes are discussed as possible new practices, empowered regulations, or adaptive measures; and eventually towards paradigm shifts. A total of 50 participants contributed to the selection, identification, and assessment of these potential changes. The findings from this study feed into the assessment of ongoing and forthcoming changes as a result of the current pandemic, specifically on two sectors of ‘construction’ and ‘the built environment’. These will include paradigm shifts in architecture practices, civil engineering practices, project management, and urbanism. Some of the suggestions in this study may harness shared practices, and some may simply develop into new forms of development practices in both sectors.